Silencing of ATP synthase β reduces phytoplasma multiplication in a leafhopper vector. (January 2021) - Galetto, Luciana; Abbà, Simona; Rossi, Marika; Ripamonti, Matteo; Palmano, Sabrina; Bosco, Domenico; Marzachì, Cristina
Graphical abstract: Highlights: RNAi in the phytoplasma vector Euscelidius variegatus is long-lasting. Silencing of ATP synthase β transcript reduces expression of the cognate protein. dsRNA injection generates siRNAs mapping only on the fragment used to design dsRNAs. Silenced insects acquire chrysanthemum yellows and Flavescence dorée phytoplasmas. Silencing of ATP synthase β reduces the multiplication of both phytoplasmas. Abstract: The leafhopper Euscelidius variegatus is a natural vector of the chrysanthemum yellows phytoplasma (CYp) and a laboratory vector of the Flavescence dorée phytoplasma (FDp). Previous studies indicated a crucial role for insect ATP synthase α and β subunits during phytoplasma infection of the vector species. Gene silencing of ATP synthase β was obtained by injection of specific dsRNAs in E. variegatus . Here we present the long-lasting nature of such silencing, its effects on the small RNA profile, the significant reduction of the corresponding protein expression, and the impact on phytoplasma acquisition capability. The specific transcript expression was silenced at least up to 37 days post injection with an average reduction of 100 times in insects injected with dsRNAs targeting ATP synthase β (dsATP) compared with those injected with dsRNAs targeting green fluorescent protein (dsGFP), used as negative controls. Specific silencing of this gene was also confirmed at protein level at 15 days after the injection. Total sRNA reads mapping to dsATP and dsGFP sequences in analysed libraries showed in both cases a peak of 21 nt, a length consistent with the generation of dsRNA-derived siRNAs by RNAi pathway. Reads mapped exclusively to the fragment corresponding to the injected dsATPs, probably indicating the absence of a secondary machinery for siRNA synthesis. Insects injected either with dsATP or dsGFP successfully acquired CYp and FDp during feeding on infected plants. However, the average phytoplasma amount in dsATP insects was significantly lower than that measured in dsGFP specimens, indicating a probable reduction of the pathogen multiplication when ATP synthase β was silenced. The role of the insect ATP synthase β during phytoplasma infection process is discussed.